1988
DOI: 10.1164/ajrccm/138.6.1515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intermittent Long-term Negative-Pressure Ventilation in Patients with Severe Chronic Obstructive Pulmonary Disease

Abstract: We tested the hypothesis that intermittent ventilatory assistance in patients with severe chronic obstructive pulmonary disease (COPD) improves pulmonary function and exercise capacity. Twenty stable patients with severe COPD were recruited from outpatient pulmonary clinics and were randomized to use a poncho wrap, negative-pressure ventilator or to receive standard care. After 6 months, the patients receiving standard care were switched over to the ventilator and vice versa, and follow-up was continued for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 6 publications
4
34
1
1
Order By: Relevance
“…In contrast with the two previous studies, ZIBRAK et al [47] showed no improvement in pulmonaryfunction test, blood gases and exercise endurance in a group of 20 stable patients with severe COPD (Pa,CO 2= 6.4¡1.3 kPa (48¡10 mmHg)) treated with poncho-wrap ventilator for 2-6 h a day for 6 months. However, 11 of the 20 patients dropped out the study because of intolerance of the ventilator, and all but one of the nine patients who completed the study expressed dissatisfaction with it.…”
Section: Long-term Application Of Negative Pressure In Stable Conditionsmentioning
confidence: 58%
See 2 more Smart Citations
“…In contrast with the two previous studies, ZIBRAK et al [47] showed no improvement in pulmonaryfunction test, blood gases and exercise endurance in a group of 20 stable patients with severe COPD (Pa,CO 2= 6.4¡1.3 kPa (48¡10 mmHg)) treated with poncho-wrap ventilator for 2-6 h a day for 6 months. However, 11 of the 20 patients dropped out the study because of intolerance of the ventilator, and all but one of the nine patients who completed the study expressed dissatisfaction with it.…”
Section: Long-term Application Of Negative Pressure In Stable Conditionsmentioning
confidence: 58%
“…All negative-pressure ventilators restrict motion and back pain is a common problem. NPV has been associated with rib fractures and pneumothorax [47]. In the study by CORRADO et al [9], two of 26 (8%) patients reported uneasiness and back pain and two others experienced vomiting during NPV.…”
Section: Advantages Contraindications and Side-effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of negative pressure devices at home and during sleep in patients with COPD has been largely unsuccessful [3,5]. In two controlled trials, patients were generally unable to sleep during negative pressure ventilation, and most either failed to complete the protocol because of lack of improvement or discomfort associated with the use of the equipment [5], or did not wish to continue treatment after the study was completed [3]. Negative pressure devices are cumbersome and relatively inefficient, particularly when the impedance to inflation is high, and may not be able to provide adequate ventilation during sleep.…”
Section: Mw Elliottmentioning
confidence: 99%
“…eucapnic) emphysematous patients. However, randomized trials failed to prove efficiency of this treatment and compliance was poor [24,25]. A previous controlled, randomized study [26] showed no beneficial effects on arterial blood gases, walking tests, level of dyspnoea, and quality of life in 184 COPD patients treated during 12 weeks with effective negative intermittent pressure ventilation by poncho, as compared to a sham ventilation with poncho.…”
Section: Negative Pressure Ventilationmentioning
confidence: 99%